Perceptual Categories Derived from Reid’s “Common Sense” Philosophy - Reeves, Adam; Dresp-Langley, Birgitta (Frontiers in Psychology, 2017)
The eighteenth-century Scottish ‘common sense’ philosopher Thomas Reid argued that perception can be distinguished on several dimensions from other categories of experience, such as sensation, illusion, hallucination, mental images, and what he called ‘fancy’. We extend his approach to eleven mental categories, and discuss how these distinctions, often ignored in the empirical literature, bear on current research. We also score each category on five properties (ones abstracted from Reid) to form a 5x11 matrix, and thus can generate statistical measures of their mutual dependencies, a procedure that may have general interest as illustrating what we can call ‘computational philosophy’.